Enhancing eco-safe driving behaviour through the use of in-vehicle human-machine interface: A qualitative study. (June 2017) - Vaezipour, Atiyeh; Rakotonirainy, Andry; Haworth, Narelle; Delhomme, Patricia
Highlights: User-centred qualitative study of eco-safe in-vehicle feedback systems. Systems designed with drivers in mind can achieve high levels of acceptance. Perceived usefulness of systems primarily influenced by monetary savings. Systems must allow user customisation of feedback. Potential issues include distraction and impact on safety. Abstract: Background: The widespread reliance on motor vehicles has negative effects on both the environment and human health. The development of an innovative in-vehicle human-machine interface (HMI) has the potential to contribute to reducing traffic pollution and road trauma. Aim: A qualitative study, using a driver-centred design approach, was carried out to test how best to provide ecological and safe (eco-safe) driving advice and feedback to drivers on their driving style via an in-vehicle HMI. Method: A total of 34 drivers ( 52.9% males ), aged 19–61 years, participated in focus groups which explored concepts from the Technology Acceptance Model (Davis, 1989). Findings: Main themes emerging from the focus groups were: (i) perceived importance of eco-safe driving behaviour; (ii) perceived usefulness of eco-safe in-vehicle HMIs; (iii) intentions to use an eco-safe in-vehicle HMI; (iv) perceptions toward eco-safe in-vehicle HMI design characteristics; and (v) potential problems associated with using eco-safe in-vehicle HMIs. Implications: This study provides the foundation to inform the design and development of an evidence-based in-vehicle eco-safe HMI with high levels of driver acceptance. Recommendations for future research are also discussed.